2022
DOI: 10.1038/s41419-022-04687-y
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β / PKC-dependent alterations in NMDA receptor composition are detected in early stages of Alzheimer´s disease

Abstract: Amyloid beta (Aβ)-mediated synapse dysfunction is an early event in Alzheimer’s disease (AD) pathogenesis and previous studies suggest that NMDA receptor (NMDAR) dysregulation may contribute to these pathological effects. Although Aβ peptides impair NMDAR expression and activity, the mechanisms mediating these alterations in the early stages of AD are unclear. Here, we observed that NMDAR subunit NR2B and PSD-95 levels were aberrantly upregulated and correlated with Aβ42 load in human postsynaptic fractions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…We have previously observed that Aβ oligomer-induced PKC phosphorylation is mediated by integrin β1 in astrocytes and in neurons [ 38 ]. Further, Aβ oligomers lead to NR2B subunit upregulation on neuronal membranes through the PKC signaling pathway [ 46 ]. Under these circumstances, integrin β1 transduces the message that Aβ oligomers brings, generating a cellular response which manifests itself in a higher permeability for calcium ions to alter cellular homeostasis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously observed that Aβ oligomer-induced PKC phosphorylation is mediated by integrin β1 in astrocytes and in neurons [ 38 ]. Further, Aβ oligomers lead to NR2B subunit upregulation on neuronal membranes through the PKC signaling pathway [ 46 ]. Under these circumstances, integrin β1 transduces the message that Aβ oligomers brings, generating a cellular response which manifests itself in a higher permeability for calcium ions to alter cellular homeostasis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, Aβ oligomers lead to NR2B subunit upregulation on neuronal membranes through the PKC signaling pathway [ 46 ]. Under these circumstances, integrin β1 transduces the message that Aβ oligomers brings, generating a cellular response which manifests itself in a higher permeability for calcium ions to alter cellular homeostasis [ 46 ]. Hence, depending on the stimulus or ligands, the same receptor along with its intracellular signaling molecules can switch on/off different pathways that lead to antagonistic cellular responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies indicate that this increased excitation is due at least in part to dysfunction in the glutamatergic system in the cortex and hippocampus ( Danysz and Parsons, 2012 ; Ghatak et al, 2019 ; Yuan et al, 2022 ). Elevated glutamate levels in the cerebrospinal fluid (CSF), increased glutamate receptor expression and activity, and decreased glutamate clearance as well as increased release, have all been found to contribute to the neuronal hyperactivation observed in AD ( Figure 1 ; Li et al, 2009 ; Pirttimaki et al, 2013 ; Talantova et al, 2013 ; Madeira et al, 2018 ; Ghatak et al, 2019 ; Zott et al, 2019 ; Ortiz-Sanz et al, 2022 ).…”
Section: Development Of E/i Imbalance In Admentioning
confidence: 99%
“…In addition to AMPA receptors and mGluRs, NMDA receptors play arguably the most important role in excitotoxic damage and E/I imbalance. While glutamatergic neurotransmission via synaptic NMDA receptors is critical for induction of long-term potentiation (LTP) and survival of neurons in several brain areas, excessive NMDA receptor activity (especially extrasynaptic NMDA receptors) contributes to aberrant gene transcription and excitotoxic pathways leading to synaptic damage, neurodegeneration and cognitive decline in AD and in other neurologic diseases ( Hardingham et al, 2002 ; Lipton, 2006 ; Alberdi et al, 2010 ; Danysz and Parsons, 2012 ; Talantova et al, 2013 ; Wang and Reddy, 2017 ; Ghatak et al, 2021b ; Ortiz-Sanz et al, 2022 ). In contrast, physiological synaptic NMDA receptor activity leads to gene expression that opposes these destructive processes ( Hardingham et al, 2002 ; Hardingham and Bading, 2010 ).…”
Section: Development Of E/i Imbalance In Admentioning
confidence: 99%